Molecular Insights into Tau Pathology and its Therapeutic Strategies in Alzheimer's Disease - Futao Zhou; Yushi Zhao; Yangyan Sun; Wanjiao Chen (Journal of Integrative Neuroscience)
Alzheimer’s disease (AD) is the most common cause of dementia. The two major hallmarks of this disease are extracellular amyloid plaques and intracellular neurofibrillary tangles in the brain, accompanied by loss of neurons and synapses. The plaques and tangles mainly consist of amyloid-β (Aβ) and tau protein, respectively. Most of the therapeutic strategies for AD to date have focused on Aβ. However, there is still no effective therapy available. In recent years, the clinical therapeutic failure of targeting Aβ pathology has resulted in increased interest towards tau-based therapeutics. In the current review, we focus on the research progress regarding the pathological mechanisms of tau protein in this disease and discuss tau-targeting therapeutic strategies.